Molecular Docking Study of Garcinia mangostana (Mangosteen) Compounds as SARS-CoV-2 Potential Inhibitors - Putri Mahirah Afladhanti; Muhammad Despriansyah Romadhan; Haidar Ali Hamzah; Qherine Bhelqis (Fakultas Kedokteran Universitas Sriwijaya, 2022)
COVID-19 pandemic poses a challenge for researchers all over the world to find effective drugs. Previous studies had identified the role of Mpro, TMPRSS2, RdRp, and ACE2 which are useful as promising drug targets to inhibit SARS-CoV-2. This study aimed to identify the potential compounds derived from Garcinia mangostana (mangosteen) as potential SARS-CoV-2 inhibitors using a molecular docking study. A total of 6 compounds of mangosteen such as 8-desoxygartanin, α-mangostin, β-mangostin, Ƴ-mangostin, garcinon e, and gartanine were used in this study. N-acetylcysteine (NAC), nafamostat, remdesivir, and lopinavir were also used as comparative drugs. Compounds and comparative drugs were docked on Mpro, TMPRSS2, RdRP, and ACE2 using AutodocTools 1.5.6 and Autodock Vina. The visualization of molecular interactions was carried out by Discovery Studio v16. All compounds met the criteria as drugs based on Lipinski’s solubility test and were safe to use based on toxicity test with admetSAR. Docking results showed that all compounds had an affinity to all receptor targets. 8-Desoxygartanin showed strong molecular interactions compared to the comparative drugs with binding energies of -8.0, -9.6, - 7.8, and -8.6 kcal/mol for Mpro, TMPRSS2, RdRp, and ACE2, respectively. All compounds have the potential to be developed as potential inhibitors through inhibiting Mpro, TMPRSS2, RdRp, and ACE2. Therefore, in vitro and in vivo investigations are needed to bring these compounds to the clinical setting.